2019
DOI: 10.1016/j.trac.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

NMR and MS-based Stable Isotope-Resolved Metabolomics and applications in cancer metabolism

Abstract: There is considerable interest in defining metabolic reprogramming in human diseases, which is recognized as a hallmark of human cancer. Although radiotracers have a long history in specific metabolic studies, stable isotope-enriched precursors coupled with modern high resolution mass spectrometry and NMR spectroscopy have enabled systematic mapping of metabolic networks and fluxes in cells, tissues and living organisms including humans. These analytical platforms are high in information content, are complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(83 citation statements)
references
References 161 publications
(149 reference statements)
0
83
0
Order By: Relevance
“…Stable isotopes especially 13 C, 15 N, and 2 H (D) are fully biologically compatible and isotopically enriched substrates can be administered with no or minimal biological effects. Stable isotope tracing of metabolic pathways has been demonstrated in a wide variety of biological systems [32,[91][92][93][94][95][96][97] for the reconstruction of metabolic networks [98][99][100] and also, in some cases, mapping of metabolic flux [77,90,91,[101][102][103][104][105][106].…”
Section: Stable Isotope Resolved Metabolomics (Sirm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Stable isotopes especially 13 C, 15 N, and 2 H (D) are fully biologically compatible and isotopically enriched substrates can be administered with no or minimal biological effects. Stable isotope tracing of metabolic pathways has been demonstrated in a wide variety of biological systems [32,[91][92][93][94][95][96][97] for the reconstruction of metabolic networks [98][99][100] and also, in some cases, mapping of metabolic flux [77,90,91,[101][102][103][104][105][106].…”
Section: Stable Isotope Resolved Metabolomics (Sirm)mentioning
confidence: 99%
“…We have begun to develop the above described approaches to investigate metabolic interactions between human lung cancer cells and Mφ in spheroid co-cultures. We have also introduced mSIRM [97,107,121,170] in our studies to maximize information retrieval from limited samples and to minimize batch artifacts. The following describes some preliminary findings that illustrate the value of these approaches.…”
Section: D Spheroids and Organoidsmentioning
confidence: 99%
“…As life is built upon carbon chemistry, carbon-13 is a stable isotope tracer frequently used in NMR and MS metabolomics studies [ 69 , 70 , 71 ]. In NMR, individual 13C atoms can be tracked through isotopomers, i.e., isomers that differ only by the position of 13C, and followed over chemical transformations of metabolic pathways.…”
Section: Metabolic Phenotyping Of Cell Culture Metabolism: Analytimentioning
confidence: 99%
“…In fluxomics experiments, culture cells are put in contact with 13C-labelled substrates, such as glucose, and 13C labeled product metabolites are quantified either by NMR or MS. This permits a very precise quantification of fluxes of matter along metabolic pathways [ 70 , 72 ]. Using this approach, direct impacts of a perturbation, be it a chemical added to the cell culture or a genetic mutation, can be identified.…”
Section: Metabolic Phenotyping Of Cell Culture Metabolism: Analytimentioning
confidence: 99%
“…Metabolomics is a very powerful tool that provide a more comprehensive understanding of the effects of biological potential at a specified time in particular environmental conditions [ 12 ]. With the development in the last few decades of analytical instruments, such as mass spectrometry and nuclear magnetic resonance spectroscopy, metabolomic analysis of cells has been widely used to perform a complete assessment of functional cellular responses to pathogen infections, toxicity and environmental factors [ 13 ]. In addition, studies have reported that metabolites directly initiate cell signaling stages and regulate various biological processes such as post-translational modifications and epigenetic mechanisms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%